(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The article considers the theoretical aspects of the influence of the company’s social responsibility on building long-term relationships with consumers in the framework of interaction marketing. The relationship between perceived social responsibility and such factors that form consumer loyalty as trust, satisfaction and involvement of consumers is shown. The importance of increasing the level of perceived social responsibility of the company is substantiated.